Paper-pen peer-correction versus wiki-based peer-correction - Froldova Vladimira (Journal of Language and Cultural Education, 2016)
This study reports on the comparison of the students’ achievement and their attitudes towards the use of paper-pen peer-correction and wiki-based peer-correction within English language lessons and CLIL Social Science lessons at the higher secondary school in Prague. Questionnaires and semi-structured interviews were utilized to gather information. The data suggests that students made considerable use of wikis and showed higher degrees of motivation in wiki-based peer-correction during English language lessons than in CLIL Social Science lessons. In both cases wikis not only contributed to developing students’ writing skills, but also helped students recognize the importance of collaboration.